Pengaruh Digital Marketing dan Aksesibilitas terhadap Minat Berkunjung ke Tasta Zoo - I Gede Phio Ananta Karna; Ni Putu Nina Eka Lestari (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2026)
In the era of digital transformation, tourism destinations must adapt to changing consumer behavior to remain competitive. Despite various marketing efforts, Tasta Zoo in Bali has not yet achieved the expected increase in visitor numbers, indicating potential gaps in its marketing strategy and accessibility. This study aims to examine the influence of digital marketing and accessibility on tourists’ visiting interest in Tasta Zoo. Using a quantitative approach, data were collected through questionnaires distributed to 100 respondents who had visited the destination. The analysis was conducted using multiple linear regression with SPSS. The results show that both digital marketing and accessibility have a positive and significant effect on visiting interest, either partially or simultaneously. These findings suggest that well-managed digital marketing through social media engagement, online advertising, and user-generated content, along with improved physical access and supporting facilities, can enhance tourists’ intention to visit. The study provides practical insights for tourism managers to strengthen their digital presence while ensuring visitor convenience through better accessibility.